Experimental and model study on dynamic behaviour and fatigue damage of tunnel invert. (15th November 2016) - Liu, Ning; Peng, Limin; Shi, Chenghua; Lei, Mingfeng
Highlights: Strain and damage changes of invert under different stress levels was elaborated. Established model can effectively reflect the relationship between damage and stress. Vibration amplitude have obvious effects on TIC fatigue behaviour. Fatigue life in this paper is much higher than that in three point bending test. Abstract: The growth of train axle loads enhances the dynamic response of the invert of a tunnel, and affects the damage behaviour of tunnel invert concrete. This article focuses on the fatigue damage of tunnel invert concrete under a cyclic bending load. The fatigue behaviour of the tunnel invert concrete under multi-directional loading is experimentally investigated in this work. The effect of the vibration amplitude is first investigated by comparing the strain and damage evolution in the tunnel's mechanical environment. Combined with the expression of S-N, a new fatigue damage model including a stress level parameter is proposed. The model parameters are also given and redefined to quantify the effect of the vibration amplitude and invert mechanical condition. Based on the experimental results, it is found that the vibration amplitude has a significant effect on the damage increment of tunnel invert concrete. The observed process of fatigue damage is similar to that of strain variation, and the whole process can be divided into three different stages, initial growth stage I, slow growth stage II, and rapid growth stage III. When the stress level is higher than 0.6, the damage and dynamic strain increases nonlinearly and fatigue failure occurs. Moreover, the fatigue life of tunnel invert concrete is 10 times more than that of the concrete under the three-point bending condition.